Field study 4 : exploring the curriculum - Borabo, Milagros L.; Borabo, Heidi Grace L. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2010)
As for its objectives, this revised Workbook on Field Study 4 aims to align teacher education with the CHED-prescribed new teacher education curriculum that is reflective of the National Competency-Based Teacher Standards. This Workbook closely adheres to the Experiential Learning Courses Handbook, a project of the Teacher Education Council (TEC) Department of Education. The Classroom observations, activities for the analysis, reflection and portfolio phases of the episodes are meant to bridge the gap between theory and practice. These activities also serve as an advocacy for current trends in education such as reflective education, multiple intelligences, and multicultural education, interactive and brain-based teaching, and authentic assessment.
Foreword iii -- Preface v -- Letter to the Field Study Student vii -- Letter to the Field Study Techer viii -- Orientation Notes for Field Study and this Workbook ix -- Suggested Guidelines for Field Study Students xiv -- Field Study 4: Exploring the Curriculum 1 -- FS 4: Episode - Look Deeper into the Concepts, Nature and Purposes of the Curriculum 4 -- FS 4: Episode 2 - What's the Curriculum Made Of? 13 -- FS 4: Episode 3 - What's New in Teaching and Learning? 22 -- FS 4: Episode 4 - Let's Craft the Curriculum 31 -- FS 4: Episode 5 - What's the Basic of the Curriculum? 35 -- FS 4: Episode 6 - Tell me your Features 44 -- FS 4: episode 7 - The Wh- of the Curriculum 53 -- FS 4: Episode 8 - What's New in the Curriculum 60.
Keywords: EDUCATION -- PHILIPPINES